Uji Ketepatan Rumus Winter Terhadap Bobot Badan Sapi Bali Flores - Villandasari, Hokiy Novia; Suparman, Paulus; Setyaningrum, Agustinah (ANGON: Journal of Animal Science and Technology, 2019)
Background. The purpose of this research is to test the accuracy of Winter formula for estimating body weight and get winter modification formula for Bali Flores cattle. Materials and Methods. Study has been done by using survey method. The material for this research by using 30 bulls which age about 2 years old with medium size weight. Parameter examined are body weight, body length, and heart girth. Data analysis has been done by using paired sample t-test. Results. The result of this research shows Winter formula is the most suitable for Bali Flores cattle is by replacing denominator into 323. Simpulan. Modified Winter formula can be used as the alternative of Bali Flores cattle body weight estimation.